Keragaman Morfometrik dan Gen cytochrome b DNA Mitokondria Ompok hypopthalmus di DAS Batang Hari. - Singkam, Abdul Rahman; Solihin, Dedy Duryadi; Affandi, Ridwan (Universitas Jambi, 2018)
This research aims to analyse the variation on morphometric and cytochrome b (cyt b) DNA mitocondria gene of Ompok hypopthalmusin Batang Hari river. Cyt b DNA mitocondria gene was amplified by polymerase chain reactionand targeted1104bp nucleotids. The results show there is no significant differentiation on morphometric structure of the samples. This result is consistent for both of morphometric (p=0.96) and index (p=0.99). Amplification of cyt b DNA mitocondria gene generates927 bp nucleotids with cytosin as the majour component and guanin as the lowest. Only one nucleotide(0.11%) is vary among all the sequences i.e.883thof the partial cyt b gene. The 883th nucleotidein O. hypopthalmus Simpang and Sungai Bengkal is guanin, while inMandiangin dan Pelayangan is adenin. This subtitution occured on the first codon and changed the 295th putative amino acid ofcyt b gene. The putative amino acid in O. hypopthalmus Simpang-Sungai Bengkal is alanina (GCC), while inMandiangin-Pelayangan is treonina (ACC).